2016
DOI: 10.1111/nmo.12736
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial: a controlled pilot trial of the 5‐HT4 receptor agonist revexepride in patients with symptoms suggestive of gastroparesis

Abstract: Four weeks of revexepride treatment did not improve symptoms or gastric emptying over placebo in patients with symptoms suggestive of gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…A symptom questionnaire-the Gastroparesis Cardinal Symptom Index (GCSI)-originally developed through patient interviews, was validated in university-based clinical practices for assessing symptoms in gastroparesis. 5,6 The GCSI has a two-week recall and is the most frequently used symptom severity measure in gastroparesis clinical trials and other clinical studies, [7][8][9][10][11][12][13][14][15][16][17][18][19] including the National…”
Section: Introductionmentioning
confidence: 99%
“…A symptom questionnaire-the Gastroparesis Cardinal Symptom Index (GCSI)-originally developed through patient interviews, was validated in university-based clinical practices for assessing symptoms in gastroparesis. 5,6 The GCSI has a two-week recall and is the most frequently used symptom severity measure in gastroparesis clinical trials and other clinical studies, [7][8][9][10][11][12][13][14][15][16][17][18][19] including the National…”
Section: Introductionmentioning
confidence: 99%
“…27 Unfortunately, the drug had no significant effect on symptoms when compared with placebo. This is not surprising considering that many patients may have had normal emptying to begin with, along with the now well-established lack of correlation between a prokinetic effect and improved symptoms.…”
Section: Update and Discussion Of Recent Studiesmentioning
confidence: 99%
“…Several 5-HT receptor agonists/antagonists, such as cisapride (5-HT4 agonist, 5-HT2, and 5-HT3 antagonist), tegaserod (5-HT4 and 5-HT1 agonist, 5-HT2a/b antagonist), mosapride (5-HT4 agonist, 5-HT3 antagonist) and revexepride (5-HT4 agonist) have been evaluated for the treatment of dyspepsia and gastroparesis, although not all studies show efficacy (114)(115)(116). A recent metanalysis showed that FD patients treated with serotonin receptor agonists have a significantly better symptom response compared to placebo (117) and the most recently published evidence indicates efficacy for prucalopride in idiopathic gastroparesis and emerging efficacy for velusetrag in gastroparesis (118,119).…”
Section: Serotonin (5-ht)mentioning
confidence: 99%